Lego Harry Potter character encyclopedia - Dowsett, Elizabeth (New York, NY : DK Publishing, 2023)
Introduces more than 200 Lego minifigures from the Lego Harry Potter world.
Wizarding World--Front cover.
7.2
3-6
Keywords: LEGO toys -- Juvenile literature; Potter, Harry -- (Fictitious character) -- Juvenile literature; Rowling, J. K. -- Characters -- Juvenile literature; LEGO toys; Potter, Harry -- (Fictitious character); Rowling, J. K. -- Characters